Phonetics or phonology? The case of falling contours in County Galway English - Airelle Théveniaut; Sophie Herment (Anglophonia)
The starting point of this research is the hypothesis that Irish might have an influence on Irish English at the intonational level. Three types of sentences (declaratives, WH-Questions and Yes-No Questions) are studied based on the PAC-Galway corpus: 33 speakers from two locations, Galway and Gaeltachtaí (Irish-speaking areas), and with a varying use of Irish. Three recurrent contours emerge of the data: H*L % (simple fall), H* L% (late fall) and L* % (low static tone), all three belonging to the category of falls. However, the three contours are distributed among the three types of sentences, this finding raising the issue of the phonetic or phonological status of these contours. The variables of location and use of Irish were therefore tested, but the hypothesis of the influence of Irish on English intonation was not confirmed. Gender and age were then taken into consideration, showing that the latter parameter seems to have an influence on the realisation of the various falling patterns, and arguing for the phonetic status of these contours.